Brand experience and brand trust: an impact towards customer brand loyalty in theme park service industry - Azman, Qistina; Saad, Mazni (2019)
Theme park industry seems to have potential in sustaining its products and services through brand recognition by the public and also tourists. However, it is hard to sustain the industry due to the lack of loyal customers as they are seeking for unique and lasting experiences from theme park brand. Lack of safety and security management by the theme park operators also contributed to trust issues towards the theme park brand. Therefore, this paper aims to identify the impact of brand experience and brand trusts towards achieving brand loyalty in a theme park. In such, it is important for theme park organiser to manage the customer brand experience and brand trust towards the theme park brand so that theme park closure issue can be avoided. The study was carried out by conduting a survey around 300 respondents who is living in adjacent to Selangor and regression analysis in SPSS was used to analyse the impact of brand experience and brand trusts towards customer loyalty in a theme park.